PERSEPSI SISWA TERHADAP EFEKTIVITAS PEMBELAJARAN GURU PPKN DI SMK NEGERI 1 TANDUN KECAMATAN TANDUN KABUPATEN ROKAN HULU - Mitra Elvira Sari; Sri Erlinda; Haryono Haryono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research is motivated by the fact that in the field, the learning process is currently not being paid attention by the teacher and is sometimes often ignored, this is as is often found in the learning process which shows that the interaction between teachers and students is less effective and efficient which results in less enjoyable learning processes. students are less active, in learning, so the material conveyed is less absorbed by students so that it affects student grades. The formulation of the problem in this study is How Students' Perceptions of Learning Effectiveness of PPKn Teachers at SMK Negeri 1 Tandun, Tandun District, Rokan Hulu Regency. This study aims to determine students' perceptions of the effectiveness of PPKn teacher learning at SMK Negeri 1 Tandun, Tandun District, Rokan Hulu Regency. The benefit of the research results is that it can be used as a school reference for updating or developing learning processes, learning media and so on, especially in PPKn subjects. This research was conducted from June to December 2020. The sampling technique was proportional sampling technique. The sample in this study amounted to 115 people. The data collection techniques used were questionnaire, interview and documentation techniques. In analyzing the data, researchers used quantitative descriptive methods. The results of this study indicate that the percentage of respondents who answered Very Good + Good was 61.5% where the Good Category was in the range 50.01-75%. It can be concluded that students' perceptions of the effectiveness of PPKn teacher learning at SMK Negeri 1 Tandun, Tandun District, Rokan Hulu Regency are in the